A hypomorphic Egfr allele does not ameliorate the palmoplantar keratoderma caused by SLURP1 deficiency. Issue 11 (27th July 2017) - Allan, Christopher M.; Tran, Deanna; Tu, Yiping; Heizer, Patrick J.; Young, Lorraine C.; Fong, Loren G.; Beigneux, Anne P.; Young, Stephen G.
Abstract: Mutations in SLURP1, a secreted protein of keratinocytes, cause a palmoplantar keratoderma (PPK) known as mal de Meleda . Slurp1 deficiency in mice faithfully recapitulates the human disease, with increased keratinocyte proliferation and thickening of the epidermis on the volar surface of the paws. There has long been speculation that SLURP1 serves as a ligand for a receptor that regulates keratinocyte growth and differentiation. We were intrigued that mutations leading to increased signalling through the epidermal growth factor receptor (EGFR) cause PPK. Here, we sought to determine whether reducing EGFR signalling would ameliorate the PPK associated with SLURP1 deficiency. To address this issue, we bred Slurp1 ‐deficient mice that were homozygous for a hypomorphic Egfr allele. The hypomorphic Egfr allele, which leads to reduced EGFR signalling in keratinocytes, did not ameliorate the PPK elicited by SLURP1 deficiency, suggesting that SLURP1 deficiency causes PPK independently (or downstream) from the EGFR pathway.